2010
DOI: 10.1007/s10530-010-9701-3
|View full text |Cite
|
Sign up to set email alerts
|

Yellow crazy ant (Anoplolepis gracilipes) invasions within undisturbed mainland Australian habitats: no support for biotic resistance hypothesis

Abstract: Ants are highly successful invaders, especially on islands, yet undisturbed mainland environments often do not contain invasive ants, and this observation is largely attributed to biotic resistance. An exception is the incursion of Yellow crazy ant Anoplolepis gracilipes within northeast Arnhem Land. The existence of A. gracilipes within this landscape's intact environments containing highly competitive ant communities indicates that biotic resistance is not a terminally inhibitory factor mediating this ant's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 73 publications
0
58
0
Order By: Relevance
“…There is little and ambiguous information on the role of native ant species in conferring biotic resistance to the invasion of exotic ant species. Both Way (1953) and Hoffmann and Saul (2010) concluded that habitat suitability, and not the presence of native ants, is the strongest predictor of invasive A. gracilipes distribution. The invasion of other ants, such as the Argentine ant L. humile in Portugal, however, was prevented by dominant native ants in cork oak plantations and pasture habitat (Way et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little and ambiguous information on the role of native ant species in conferring biotic resistance to the invasion of exotic ant species. Both Way (1953) and Hoffmann and Saul (2010) concluded that habitat suitability, and not the presence of native ants, is the strongest predictor of invasive A. gracilipes distribution. The invasion of other ants, such as the Argentine ant L. humile in Portugal, however, was prevented by dominant native ants in cork oak plantations and pasture habitat (Way et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hoffmann and Saul (2010) showed that habitat suitability is the primary determinant of A. gracilipes incursions, and climatic variables, especially temperature and humidity, are important factors determining ant distribution (Torres 1984;Porter 1988;Hölldobler and Wilson 1990;Krushelnycky et al 2005). In the Vallée de Mai, higher humidity and temperature and lower canopy cover were correlated with A. gracilipes presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In northern Australia, 62% of species collected co-existed with A. gracilipes and the relative contribution of ants smaller than A. gracilipes to total abundance and species richness was always greater in infested sites [26]. All quantitative studies within the Seychelles have found many ant species smaller than A. gracilipes coexisting with the invader, but not the considerably larger species O. simillimus [40], [48], [49].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike A. gracilipes invasions in Samoa (Savage et al, 2009) and on Christmas Island (O'Dowd et al, 2003), carbohydrate resources are not an obvious driver of differences in abundance (authors' unpublished data), nor are there clear associations with anthropogenic disturbance (Hoffmann & Saul, 2010). Unlike A. gracilipes invasions in Samoa (Savage et al, 2009) and on Christmas Island (O'Dowd et al, 2003), carbohydrate resources are not an obvious driver of differences in abundance (authors' unpublished data), nor are there clear associations with anthropogenic disturbance (Hoffmann & Saul, 2010).…”
Section: Introductionmentioning
confidence: 99%